A bird´s-eye view of chromosomes during meiotic prophase I - Pigozzi, Maria Ines (2022)
The present review aims to summarize the research carried out in relation to meiosis in birds, especially by observing the protein axes of the chromosomes in prophase I of meiosis. This line of research, initially developed in Argentina, has provided key data in the study of the evolution of sex chromosomes and the mechanisms involved in the frequency and distribution of crossing over in birds, among other topics. Some of these contributions, in addition to those made by other authors, are described also providing the general theoretical framework or the hypotheses that support them.